1987
DOI: 10.1210/jcem-64-4-865
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Human Preovulatory Follicular Fluid*

Abstract: Melatonin, the major hormone of the pineal gland, has antigonadotrophic activity in many mammals and may also be involved in human reproduction. Melatonin suppresses steroidogenesis by ovarian granulosa and luteal cells in vitro. To determine if melatonin is present in the human ovary, preovulatory follicular fluids (n = 32) from 15 women were assayed for melatonin by RIA after solvent extraction. The fluids were obtained by laparoscopy or sonographically controlled follicular puncture from infertile women und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
151
0
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(162 citation statements)
references
References 29 publications
5
151
0
6
Order By: Relevance
“…This is consistent with the earlier reports on human and rat demonstrating the presence of MTNR1A and MTNR1B in granulosa cells and luteal cells (Soares et al 2003). The presence of high levels of melatonin in follicular fluid in human and binding sites in the ovary (Brzezinski et al 1987, Ronnberg et al 1990, Niles et al 1999 and, now, the presence of MTNR1A and MTNR1B in ovary suggest that melatonin directly acts as a modulator of ovarian functions.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the earlier reports on human and rat demonstrating the presence of MTNR1A and MTNR1B in granulosa cells and luteal cells (Soares et al 2003). The presence of high levels of melatonin in follicular fluid in human and binding sites in the ovary (Brzezinski et al 1987, Ronnberg et al 1990, Niles et al 1999 and, now, the presence of MTNR1A and MTNR1B in ovary suggest that melatonin directly acts as a modulator of ovarian functions.…”
Section: Discussionsupporting
confidence: 92%
“…Reported increases in prolificacy subsequent to the administration of melatonin in sheep might be due to the direct effect of exogenous melatonin on the ovine oocyte, which has been observed in other species (Ishizuka et al, 2000;Na et al, 2005;Parka et al, 2006). Several studies have reported the presence of melatonin in human pre-ovulatory follicular fluid and the seasonal variation of its contents (Brzezinski et al, 1987;Yie et al, 1995), and melatonin receptors have been found on rat, mouse, and porcine ovarian cells (Soares et al, 2003;Na et al, 2005;Kang et al, 2008), which suggests that melatonin has a direct effect on oocyte competence.…”
mentioning
confidence: 99%
“…The involvement of melatonin in the steroid genesis of human ovaries has been documented (19,20). Webley and Luck (19) also reported direct stimulation of melatonin on hCG.…”
Section: Discussionmentioning
confidence: 95%
“…Webley and Luck (19) also reported direct stimulation of melatonin on hCG. Melatonin was thought to enhance hCG stimulation of progesterone production by human granulosa cells in culture (20). Yie et al (21,22) reported higher concentrations of melatonin and progesterone during the dark season of the year and of oestradiol during the light season from pre-ovulatory follicular fluids.…”
Section: Discussionmentioning
confidence: 99%